Shear Stress Promotes Remodeling of Platelet Glycosylation via Upregulation of Platelet Glycosidase Activity: One More Thing - Roka-Moiia, Yana; Lewis, Sabrina; Cleveland, Estevan; Italiano, Joseph E.; Slepian, Marvin J. (Thrombosis and Haemostasis, 2024)
Mechanical circulatory support (MCS) is a mainstay of therapy for advanced and end-stage heart failure. Accompanied by systemic anticoagulation, contemporary MCS has become less thrombogenic, with bleeding complications emerging as a major cause of readmission and 1-year mortality. Shear-mediated platelet dysfunction and thrombocytopenia of undefined etiology are primary drivers of MCS-related bleeding. Recently, it has been demonstrated that deprivation of platelet surface glycosylation is associated with the decline of hemostatic function, microvesiculation, and premature apoptosis. We test the hypothesis that shear stress induces remodeling of platelet surface glycosylation via upregulation of glycosidase activity, thus facilitating platelet count decline and intense microvesiculation.Human gel-filtered platelets were exposed to continuous shear stress in vitro. Platelets and platelet-derived microparticles (PDMPs) were quantified via flow cytometry using size standard fluorescent nanobeads. Platelet surface glycosylation and NEU1 expression were evaluated using lectin- or immune-staining and multicolor flow cytometry; lectin blotting was utilized to verify glycosylation of individual glycoproteins. Platelet neuraminidase, galactosidase, hexosaminidase, and mannosidase activities were quantified using 4-methylumbelliferone-based fluorogenic substrates.We demonstrate that shear stress promotes selective remodeling of platelet glycosylation via downregulation of 2,6-sialylation, terminal galactose, and mannose, while 2,3-sialylation remains largely unchanged. Shear-mediated deglycosylation is partially attenuated by neuraminidase inhibitors, strongly suggesting the involvement of platelet neuraminidase in observed phenomena. Shear stress increases platelet NEU1 surface expression and potentiates generation of numerous NEU1+ PDMPs. Platelets exhibit high basal hexosaminidase and mannosidase activities; basal activities of platelet neuraminidase and galactosidase are rather low and are significantly upregulated by shear stress. Shear stress of increased magnitude and duration promotes an incremental decline of platelet count and immense microvesiculation, both being further exacerbated by neuraminidase and partially attenuated by neuraminidase inhibition.Our data indicate that shear stress accumulation, consistent with supraphysiologic conditions of device-supported circulation, promotes remodeling of platelet glycosylation via selective upregulation of platelet glycosidase activity. Shear-mediated platelet deglycosylation is associated with platelet count drop and increased microvesiculation, thus offering a direct link between deglycosylation and thrombocytopenia observed in device-supported patients. Based on our findings, we propose a panel of molecular markers to be used for reliable detection of shear-mediated platelet deglycosylation in MCS.
Keywords: platelet deglycosylation; shear stress; neuraminidase; mechanical circulatory support; thrombocytopenia